Pengaruh Strategi Kepemimpinan dan Manajemen Mutu Sumber Daya Manusia terhadap Kinerja Guru di Madrasah - Hasani, Syifaul Umam; Suwandi, Suwandi (Lembaga Yasin AlSys, 2025)
Education is a fundamental factor in national development, and teacher performance is a key element in improving the quality of both the educational process and outcomes. This study aims to analyze the influence of leadership strategy and human resource quality management on teacher performance at MTs Negeri 13 Jombang, both partially and simultaneously. A quantitative approach with an ex post facto design was employed, involving 32 teachers as respondents selected through a saturated sampling technique. The research instrument consisted of a questionnaire with 30 statement items, and data were analyzed using multiple linear regression. The results indicate that both leadership strategy and human resource quality management have a significant partial effect on teacher performance, with significance values below 0.005. Simultaneously, the two variables also have a significant influence, as shown by an F value exceeding the critical F table value. These findings suggest that teacher performance is strongly influenced by the effectiveness of the head of madrasah’s leadership strategy and the proper implementation of human resource quality management. The implications of this study emphasize the need to strengthen leadership capacity and human resource management systems within madrasah settings to support sustainable improvements in educational quality.